'CONTACT!': New York Philharmonic Orchestra, Milton Court Concert Hall, London. (October 2015) - Rutherford-Johnson, Tim
<x content-type="archive" xml:space="preserve">Abstract</x> The New York Philharmonic Orchestra, under its Music Director Alan Gilbert, spent a week in residence at the Barbican Centre in April, giving four concerts and various other events. Among them was 'CONTACT!', a concert of chamber music performed by members of the NYPO in the Guildhall's Milton Court Concert Hall on 18 April 2015. There were five pieces for various small groups. Three were new to the UK, and I will focus on these.